Locality-Based Administrative Services (Study in Terong Village, Kapanewon Dlingo, Bantul Regency, Unique Region of Yogyakarta) - Zulianti, Zulianti; Purnomo, Herry; Tiurmida, Nelly; Sumaryantiningsih, Siti; Marina, Rema (Universitas Widya Mataram, 2025)
The sub-district is the lowest element of government, having direct relations with the community. The district head has the authority to carry out administrative services. The administration of administrative services in sub-districts follows the Village Minimum Service Standards (SPM). The quality of the service measures the success of administrative services. Terong Village must be able to provide administrative service to users, namely the community, according to the Village SPM provisions, and provide quality services to user needs. The research aims to determine administrative services and the suitability of administrative services with the SPM Village in Terong Village. The informants in the study were the Head of Terong Village, Carik, the administrative officer of Terong Village, Dukuh, and the community user of administrative services—research analysis using analytical descriptive. The research analysis results concluded that administrative services in Terong District are locality-based services based on 1) geographical, 2) community characteristics, 3) trust in other communities, and 4) demographic factors. The results of the research show that Terong Village does not yet have a Village SPM and does not service SOPs or service announcements. Terong District has implemented SERQUAL services based on demographic factors, geography, and community characteristics. Keywords: Service; Administration; locality.